Kualitas Pelayanan Jasa Pengiriman Barang Pada J&T Express Karawang Cabang Kondang Jaya - Desi Nurmala; Vadya Marshanda Budiman; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This writing aims to determine the quality of goods delivery service at the J&T ExpressKarawang Kondang JayaBranch. The quality of goods delivery services is a key factor in meeting consumer needs and maintaining customer satisfaction. This paper focuses on key aspects of service quality, including speed of delivery, delivery security, delivery reliability, and customer service. The method used in this writing is descriptive method with observation,the results of the writing show that J&T Express Karawang Kondang Jaya Branch has a high level of customer satisfaction in terms of delivery speed. Delivery security is also valued well by customers, with an adequate packaging system to protect goods.